Regeneration of Military Brownfield Sites: A Possible Tool for Mitigating Urban Sprawl? - Bence Szabó; Tamás Kovalcsik; Zoltán Kovács (Land)
Urban sprawl and brownfields are recognized as the main challenges for sustainable land use in post-industrial cities. Using a mixed methodology (GIS and interviews), this research aimed to examine the relationship between the redevelopment process of former Soviet military brownfields and urban sprawl in Hungary. Research findings highlighted the overall importance of the regeneration of military brownfields in urban development; however, not all the assessed projects appeared to be beneficial to densification objectives. We could identify two groups of brownfields lying within the boundaries of the compact city and outside the boundaries. The regeneration of military brownfields embedded in the built-up areas of cities can contribute to densification objectives and attract new functions and residents to abandoned areas. They can also support wider regeneration strategies of local governments, especially in run-down neighborhoods. However, a large number of military brownfields are located on the peripheries of metropolitan areas. The regeneration of such sites, as demonstrated by the case studies, can play a catalyst role in urban sprawl. Therefore, it is important to emphasize that local municipalities should make a careful strategic selection of military brownfield sites for redevelopment based upon their characteristics and location, as supported by the typology presented in this study, together with locally perceived socio-economic and risk factors.